Critical Literacy in AI-Assisted Academic Writing among EFL Undergraduate Students - Angella Novitaningrum (STIT Buntet Pesantren Cirebon, 2025)
This study investigates EFL undergraduate students’ critical literacy in AI-assisted academic writing. It employed a descriptive qualitative research design to examine students’ use of AI tools, their level of critical literacy in interacting with AI-generated texts, and the challenges and opportunities encountered in AI-assisted writing environments. The participants of this study were fourth-semester undergraduate students enrolled in the English Education Study Program at STIT Miftahul Midad Lumajang, selected through purposive sampling based on their experience with AI-assisted writing. Data were collected through classroom observations, semi-structured interviews, and document analysis. The findings indicate that students integrate AI across all stages of writing, with varying levels of dependence. While AI enhances idea generation, language accuracy, and immediate feedback, students exhibit differing levels of critical literacy, ranging from passive acceptance to active evaluation and modification. Many students demonstrate moderate to low critical engagement, indicating over-reliance and limited evaluative skills, while a smaller group shows higher-order critical thinking. Overall, the study highlights the importance of fostering critical literacy to ensure that AI is used responsibly as a supportive tool rather than a substitute for cognitive engagement in academic writing.